Pendidikan Islam Perspektif Thaha Husein dalam Kitab Mustaqbal Al-Tsaqafah Fi Misr - Muhammad Fariq, Wan; Darwis, Muhajir; Nuramini, Aisyah (Al-Bahtsu: Jurnal Penelitian Pendidikan Islam, 2021)
Thaha Husein was a scholar who had been blind since childhood, but he made significant changes to the field of education in Egypt. His position as Minister of Education was used to make changes in education which had previously lost relevance to the times, slowed down human resource development, and extended foreign domination to the independence of the Egyptian state. Thaha Husein made education free, made changes to the curriculum, methods, and made education in Egypt more humanist and modern than before.